Pengaruh Promosi dan Persepsi Harga terhadap Keputusan Pembelian : Survei pada Konsumen Dua Jaya Sandal di Kota Tasikmalaya - Anita (CV. Ulil Albab Corp, 2022)
This study aims to determine the effect of promotion and price perception on purchasing decisions (Survey of Dua Jaya Sandal consumers in Tasikmalaya City). The method used is the causality method with a survey approach. With a research sample of 100 consumers at Dua Jaya Sandal Tasikmalaya. The data used is primary data. The analytical tool used in this study is Multiple Linear Regression using SPSS version 25. The results show that promotion has good criteria, price perception has good criteria for purchasing decisions at Dua Jaya Sandal Tasikmalaya. There is a simultaneous significant effect of promotion variables and price perceptions on purchasing decisions at Dua Jaya Sandal Tasikmalaya. There is a partially significant effect of the promotion variable on purchasing decisions at Dua Jaya Sandal Tasikmalaya. There is a partially significant effect of price perception variables on purchasing decisions at Dua Jaya Sandal Tasikmalaya